+0

# If x = log a (bc), y = log b (ca) and z = log c (ab) prove that

0
236
2
+21

If x = loga(bc), y = logb(ca) and z = logc(ab) prove  that

+ y +  xy-  2.

OldTimer  Sep 29, 2017
Sort:

#1
+2

3 important logarithmic identities:

1.loga(b)=1/(logb(a))

2. loga(bc)=loga(b)+loga(c)

3. loga(b)*logb(c)=loga(c)

x+y+z= loga(bc)+logb(ca)+logc(ab)=(loga(b)+loga(c))+(logb(c)+logb(a))+(logc(a)+logc(b)).

d=loga(b)

e=loga(c)

f=logb(c)

x+y+z=(loga(b)+loga(c))+(logb(c)+logb(a))+(logc(a)+logc(b))=d+e+f+1/d+1/e+1/f

x*y*z-2=(loga(b)+loga(c))*(logb(c)+logb(a))*(logc(a)+logc(b))=(d+e)*(f+1/d)*(1/e*1/f)=(d*f)/e+d+1/e+1/f+f+e+1/d+e/(d*f)-2=d+e+f+1/d+1/e+1/f+((d*f)/e+e/(d*f)-2).

d*f=loga(b)*logb(c)=loga(c)=e therefore e/(f*d)=(d*f)/e=1 meaning:

x*y*z-2=d+e+f+1/d+1/e+1/f+((d*f)/e+e/(d*f)-2)=(d+e+f+1/d+1/e+1/f)+((d*f)/e+e/(d*f)-2)=(x+y+z)+(1+1-2)=(x+y+z)+0=x+y+z

therefore x+y+z=x*y*z-2

~blarney master~

Guest Sep 29, 2017
#2
+79786
+2

Note....    logd e  *  loge f =   log f

Also .....     log e / log d   +  log f / log d  =   logd (ef)

Also........ [ log a / log c ] [ log c / log a ]  =   1

Also ...........( logb c *  logc b )  =  1

And.....    logd e + logd f  =  logd (ef)

So......

xyz  =   [  logb / loga   + log c /  log a ]  [  log c / log b  + log a / log b ] [ log a / log c + log b / log c ]  =

[ ( logb / loga)( log c / log b) + (logb / loga)( log a / log b) + ( log c /  log a)  (  log c / log b) +

(log c /  log a) (log c /  log a)]  [ log a / log c + log b / log c ]

[ loga c  + 1  +  log c /  loga *  log c / log b  +  logb c ]  [ logc a + logc b  ] =

[   loga c  + 1   +  loga c * logb c   +   logb c ]   [ logc a + logc b  ]  =

[ ( loga c) ( logc a) + (1)( logc a) + ( logc a * loga c) * logb c + (logb c)(logc a ) + ( loga c)( logc b) + (1)( logc b) + loga c *( logb c *  logc b )  +  ( logb c)(logc b )  ]

[  1 +  logc a  + 1* logb c  +  logb a  + loga b +  logc b +   loga c * 1  + 1  ]  =

[ 2  + loga b +  loga c +  logb c  +  logb a +   logc a  +  logc b ]  =

2   +  loga (bc)  + logb(ca)  + logc (ab)

2  +  x  +  y  + z           (  subtract 2 from both sides)

xyz  - 2   =  x + y + z

CPhill  Sep 29, 2017
edited by CPhill  Sep 29, 2017
edited by CPhill  Sep 29, 2017
edited by CPhill  Sep 29, 2017
edited by CPhill  Oct 4, 2017

### 23 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details